The role of personal anxiety in the development of psychophysiological indicators in adolescent athletes - A. A. Makarova; O. A. Kharkova (National Electronic Information Consortium (NEICON), 2021)
Objective: to study the role of personal anxiety in the development of psychophysiological indicators in adolescent athletes.Materials and methods. To study the prevalence of high levels of personal anxiety (hereinafter - LT), as well as to determine the characteristics of psychophysiological indicators, the study involved 23 teenagers - boys and girls who were representatives of different sports. Using the device for psychophysiological testing UPFT-1/30 "Psychophysiologist", indicators of simple visual-motor reaction and the level of LT on the Spielberg scale were obtained. To assess the impact of changes in high LT levels on psychophysiological indicators, 14 adolescent athletes with a high level of personal anxiety were selected and then divided into 2 groups. The experimental group included adolescents who wanted to participate in an experiment on the use of cognitive behavioral therapy techniques to correct high LT levels; the control group included adolescents with high LT levels who were not trained in cognitive behavioral therapy techniques.Results. Every third adolescent athlete had a high level of LT. Adolescent athletes with a high LT level, in contrast to adolescents with an optimal LT level, were less efficient, and, despite a shorter minimum reaction time, made more mistakes. The dynamics of psychophysiological indicators were observed both in the group with intervention and in the group where no cognitive behavioral therapy techniques were performed; however, after studying the difference in the physiological parameters of the central nervous system in the group where there was a change in LT, and in the group where LT either did not change or increased, we found positive changes. Changes in the LT level led to a decrease in the average reaction time, the minimum reaction time, and an increase in the level of stability of reactions.Conclusions. A high level of LT affects the psychophysiological parameters of the central nervous system in adolescent athletes. The use of cognitive behavioral therapy techniques to normalize the LT level of adolescent athletes leads to an improvement in the physiological parameters of the central nervous system.